Transforming cities by designing with communities. - Webb, Rosie; Avram, Gabriela; García, Javier Burón; Joyce, Aisling (Springer Open, 2019)
The Adaptive Governance Lab at the School of Architecture at University of Limerick has been working collaboratively with local government officials and community activists on action research projects co-designing with communities in neighbourhoods, villages and city districts in various locations in Ireland since 2010. The collaboration model developed is a genuine example of 'hackable city-making', where the local communities are involved in designing specific solutions for improving liveability in their areas, with the involvement and support of local government. A 'Designing with Communities' framework has emerged from the process in the 5 years of practice this chapter refers to. This has led to the need to refine the characterisation of the time frame, the methodologies, the commitments required from participants, the financial costs associated with the process, the advantages and disadvantages of engagement as well as the replicability of the process across cultures and governmental systems. Our chapter documents that ongoing process, defines the emerging structure of the framework, reflects on the value and risks of the process that has been carried out to date in terms of its usefulness as an urban management tool and active learning tool and proposes ways in which the framework can be adapted to fit into the developing community engagement structures of both academia and local government in Ireland.
Keywords: Stadtsoziologie; Digitalisierung; Informationstechnologie; Partizipation; Stadtgesellschaft; Stadtgestaltung; Urban Governance; Interaktion